1961
DOI: 10.1161/01.res.9.2.362
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Pressure -Volume Relationships and Myocardial Oxygen Consumption in the Isolated Heart

Abstract: HYPOTHESIS that the physical work performed during ventricular systole is largely determined hy ventricular diastolic volume has had currency for the last 45 years. 1 " 4 The oxygen cost of the heart's contraction has likewise been related to diastolic volume, and also to stroke work, mean arterial blood pressure times the heart rate, the integral of systolic pressure in time, and ventricular wall tension. 2 -3 ' r>~9 Many have attempted to identify the factors that determine the oxygen needs of the heart. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
4

Year Published

1963
1963
1992
1992

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(63 citation statements)
references
References 21 publications
6
53
0
4
Order By: Relevance
“…To validate this assumption, at least three data points (and therefore at least three ventricular angiographic studies using the methodology described above) would be required for each subject. However, in support of the assumption of linearity are the careful studies of Monroe and French, 6 Suga and Sagawa7, 8 and Weber et al0' 11 in the isolated heart, and of Mahler and co-workers in the conscious animal.9 All of these investigators found precise linearity of end-systolic pressure-volume relations over the physiologic range.…”
Section: Circulation 846mentioning
confidence: 94%
“…To validate this assumption, at least three data points (and therefore at least three ventricular angiographic studies using the methodology described above) would be required for each subject. However, in support of the assumption of linearity are the careful studies of Monroe and French, 6 Suga and Sagawa7, 8 and Weber et al0' 11 in the isolated heart, and of Mahler and co-workers in the conscious animal.9 All of these investigators found precise linearity of end-systolic pressure-volume relations over the physiologic range.…”
Section: Circulation 846mentioning
confidence: 94%
“…Ten minutes after the first ventriculogram, 10 mg of isosorbide dinitrate (ISDN) were given sublingually. Arterial pressure was recorded, and when peak systolic pressure had decreased by at least 15 mm Hg, ventriculography was repeated identically.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6] ESPVR linearity enables a simple description in terms of a slope (Ees) and volume axis intercept (V0) and of a characterization of ventricular contraction by a time-varying elastance model. However, as techniques for ESPVR determination and the condition of experimental preparations have improved, nonlinearity of the relation has been increasingly observed.…”
mentioning
confidence: 99%